Debt, Structural Adjustment and Deforestation: A Cross-National Study - John M. Shandra; Eran Shor; Gary and Bruce Maynard and London (Journal of World-Systems Research, 2015)
We present cross-national models that examine the determinants of deforestation from 1990 to 2005 for a sample of sixty-two poor nations. We test dependency theory hypotheses that both debt and structural adjustment affect forests. We find substantial support for this theoretical perspective. The results indicate that both factors increase deforestation. We also find support for world polity theory that international non-governmental organization density decreases deforestation. We conclude with a brief discussion of the findings, policy implications, and possible directions for future research.